SISTEM INFORMASI AKADEMIK SISWA PADA SMPN 1 KOTA SERANG - Andi Usri Usman; Afif Purnomo (Journal of Innovation And Future Technology (IFTECH), 2021)
The development of internet technology rapidly, as one of information medium can certainly provide an ease in accessing information for an education institution. Before growing the internet technology, information process could not be worked properly, effectively, and efficiently. By the existence the Web-based information system of student academic monitoring at SMP 1 Kota Serang, it could provide convenience system for students or parents in monitoring students’ academic involved attendance information and student academic score. Monitoring is an activity that can be described as awareness about what would like to know, the highlevel monitoring is done in order to make the measurement of time that shows the movement or away from it. Monitoring will provide information on the status and tend to that measurement and evaluation are completed repeatedly from time to time, monitoring is generally carried out for specific purposes therefore the information provided by the school may be accepted well for students and parents. This web-based information system of student academic Monitoring at SMAP 1 Kota Serang was designed by using HTML, PHP, and MySQL as based of data. While in creating system design, the writer used the structured of database design method in diagram flow data (DFD). With applying student academic Monitoring, it can overcome the existing problems and ease in process of service that can be handled quickly and efficiently.